2011
DOI: 10.3113/fai.2011.0432
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of a Locking and Nonlocking Reconstruction Plate in an Osteoporotic Calcaneal Fracture Model

Abstract: While locking plate technology has shown mechanical advantages for fracture management in other osteoporotic models, in our fracture model and plating construct, this was not found. It is still unclear which fixation technique is most beneficial in these calcaneal fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Blake et al 3 performed a similar study and also found no difference. 3 Chen et al, 10 in a retrospective comparative study, found that intra-articular calcaneal fractures treated with locking plates had a better BA at final follow-up (statistically significant at P = .002) compared with the nonlocked group (average 25.1 months in locked group and 26 months in the nonlocked group) despite similar initial postoperative BA between the 2 groups. Although the authors examined age, gender, Sanders classification, associated fractures, and osteoporosis, no multivariable linear regression analysis was performed to determine whether nonlocking constructs were an independent predictor of settling.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Blake et al 3 performed a similar study and also found no difference. 3 Chen et al, 10 in a retrospective comparative study, found that intra-articular calcaneal fractures treated with locking plates had a better BA at final follow-up (statistically significant at P = .002) compared with the nonlocked group (average 25.1 months in locked group and 26 months in the nonlocked group) despite similar initial postoperative BA between the 2 groups. Although the authors examined age, gender, Sanders classification, associated fractures, and osteoporosis, no multivariable linear regression analysis was performed to determine whether nonlocking constructs were an independent predictor of settling.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is supported by several other studies that found no difference when using locking and nonlocking plates for intra-articular calcaneus fractures. 3,18,35 Illert et al 18 performed a biomechanical study examining locking and nonlocking plate constructs in an osteoporotic bone model and found no difference in posterior facet settling between the two groups. Blake et al 3 performed a similar study and also found no difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to locking and nonlocking plates for the fixation of calcaneal fractures, some previous biomechanical studies revealed significant differences were not observed between the kinds of plates in terms of displacement of the posterior facet and the number of cycles to failure [32,33]. Concerned with the clinical outcomes in the present study, there was no significant difference between the two plating systems in terms of SF-36 (P > 0.05), which was consistent with results reported in literature [25].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these locking plates provide good coronal plane stability of the calcaneus, and they may provide stable support of the medial segment as well. So far, various kinds of biomechanical studies have been done on calcaneal fractures based on cadaver specimens or models, while the internal stress transmission mechanism of the bone stress can be difficult to reveal. Compared with the limitation of source shortage of specimens, and the inability to perform the research with different load conditions on cadaver specimens or physical models, the three‐dimensional (3‐D) finite element analysis (FEA) method has become one of the most effective approaches for biomechanical studies due to the rapid development of computer technology.…”
Section: Introductionmentioning
confidence: 99%